MENTAL ACCOUNTING DALAM KEPUTUSAN PEMBELIAN ITEM GAME ONLINE â€œMOBILE LEGENDS : BANG BANGâ€ - Sari, Azalia Elfreda; Ismawati, Anastasia Filiana (Jurnal Ekonomi Manajemen, 2022)
This research was conducted to analyze the effect of mental accounting attitude in the decision ofÂ purchasing online game items Mobile Legends: Bang Bang. Mental Accounting has a definitionÂ of how a person makes decisions in treating their finances with the ability to manage current andÂ future income. This research will analyze mental accounting with component framing effect,specificÂ control,Â selfÂ control,Â andÂ selfÂ reportÂ ofÂ purchasingÂ gameÂ onlineÂ itemsÂ MobileÂ Legends.Â TheÂ research used a descriptive method with a quantitative approach and used a mental accountingÂ theory. Sample taken out by survey questionnaire with 100 respondents distributed to teenegersÂ withÂ agesÂ 18-25Â years.Â DataÂ processingÂ willÂ beÂ carriedÂ outÂ byÂ usingÂ StructuralÂ EquationÂ ModelingÂ (SEM)withÂ PartialÂ LeastÂ SquareÂ (PLS).Â TheÂ resultsÂ ofÂ thisÂ research concludeÂ thatÂ theÂ existenceÂ ofÂ four components of mental accounting, namely the framing effect, specific control, self-control,Â andÂ self-reportÂ haveÂ aÂ positiveÂ effectÂ onÂ consumerÂ decisionsÂ in purchasingMobileÂ LegendsÂ onlineÂ game items.Â